PERSEPSI MAHASISWA TERHADAP LABORATORIUM BIOLOGI SEBAGAI PENUNJANG PERKULIAHAN DI PROGRAM STUDI PENDIDIKAN BIOLOGI STKIP YPM - Setia Wulandari Ningsih; Rivo Yulse Viza; Eni Yulianti (Pendidikan Biologi STKIP YPM Bangko, 2022)
This research is motivated by the importance of a laboratory in biology education because it is closely related to the learning process, namely practicum so the biology laboratory must be able to support lecture activities. With the existence of various laboratory facilities to date, it is not known whether these facilities can support lectures or not, because research has never been done on the role of the biology laboratory in the Biology Education Study Program of STKIP YPM in the learning process. Some aspects that must exist and be considered in a laboratory so that lecture activities can run well and achieve goals include, among others, laboratory rooms, laboratory facilities, educational equipment (props and experimental equipment), educational media, consumables, and other equipment. This study aims to determine student perceptions of the biology laboratory as support for lectures at the STKIP YPM Biology Education Study Program. This type of research is qualitative research that uses descriptive methods. The research informants were students of the Biology Education Study Program class of 2017, totaling ten people. Data collection techniques through questionnaires, observations, interviews, and documentation. There are three data analysis techniques used, namely, data reduction, data presentation, and conclusions. Based on the results of the study, it was found that students' perceptions of the biology laboratory as support for lectures in the Biology Education Study Program, STKIP YPM, scored 78.6% in the very supportive category.